Life-saving emergency clamshell thoracotomy with damage-control laparotomy. Issue 3 (4th March 2019) - Farooqui, Asif Masroor; Cunningham, Clare; Morse, Nick; Nzewi, Onyekwelu
Abstract : Clamshell thoracotomy for thoracic injuries is an uncommon emergency department procedure. The survival rates following emergency thoracotomy are very low at 9%–12% for penetrating trauma and 1%–2% for blunt trauma. We report an unusual case of survival after emergency department clamshell thoracotomy for penetrating thoracic trauma with cardiac tamponade in a 23-year-old man with multiple stab wounds on the chest and abdomen. The patient was awake and alert on arrival in the emergency department. Bilateral chest decompression by needle thoracostomy released air and blood. During subsequent chest drain insertion, the patient suddenly deteriorated and arrested. Clamshell thoracotomy was performed, and sinus rhythm restored before transfer to theatre. Following repair of the thoracic injuries, a midline laparotomy was performed as bleeding was suspected from the abdomen and a splenic injury repaired. The patient survived and has made a full recovery. This case demonstrates how clamshell thoracotomy can be a life-saving procedure.